STUDY OF SAP WATER QUALITY BASED ON VISCOSITY AND DIELECTRIC CONSTANTS - Zalpiana, Zalpiana; Bahtiar, Bahtiar; Meiliyadi, Lalu Ahmad Didik (Universitas PGRI Sumatera Barat, 2023)
This study aims to determine the quality of sap water by measuring its viscosity and dielectric constant. The sample used is pure sap water and sap water mixed with coconut water. The dielectric constant was measured using the parallel plate method while the viscosity was measured using the Oswald viscometer method. Based on the measurement results, the viscosity coefficient value of pure sap water is 1.558 Poise. The value of the viscosity coefficient decreases as the concentration of the sap water decreases where the viscosity coefficient value is 1.005 Poise for the sap water with a concentration of 50% and 0.753 Poise for the sap water with a concentration of 10%. In measuring the value of the dielectric constant, the dielectric constant of pure sap water is 7.38 x 105. The dielectric constant value of the sap water decreases with the addition of coconut water which is 4.90 x 105 at a concentration of 50%, and 3.39 x 105 at a concentration 10%. Pure sap water has a higher level of viscosity than coconut water which is indicated by a higher coefficient of viscosity compared to sap water which has been mixed with coconut water so that it is able to store more electrical energy, as a result the capacitance increases and the dielectric constant also increases.